Modelling and design of PID controller for voltage control of AC hybrid micro-grid - Ibrahim Alhamrouni; M. A. Hairullah; N. S. Omar; Mohamed Salem; Awang Jusoh; T. Sutikno (Institute of Advanced Engineering and Science, 2019)
The growing demand for power that needs to be remotely transported creates a fast and effective solution of Distributed Energy Resources (DERs) integration. Distributed Energy Resources (DERs) can lessen the electrical and physical distance between load loss and generator, transmission and distribution, and the level of carbon emissions. Such challenges can be overcome by using microgrids, which combine various types of DERs without interrupting the grid operation, allowing the power system to detect and control the errors more efficiently, allowing the shedding load and automatic switching through control algorithms so that blackouts and power restoration times are shortened, enabling either a relevant grid or islanded mode operation, and improving system reliability and flexibility via DERs. This work includes modelling of hybrid AC micro-grid as well as presenting an efficient control technique for micro-grid. In the present work the performance of hybrid AC microgrid system is analyzed in the islanded mode. Photovoltaic system and fuel cell stack are used for the development of microgrid. It also includes microgrid control objectives and the most common problems encountered and their solutions. The employed control technique is able to control the output voltage at a desired and standard value. The control strategies of the hybrid AC microgrid are simulated in MATLAB/SIMULINK.